1995
DOI: 10.1111/j.1365-3059.1995.tb02725.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in isolates of Mycogone perniciosa and in disease symptoms in Agaricus bisporus

Abstract: Eight isolates of Mycogone perniciosa, five from Agaricus bisporus and three from Agaricus arvensis, were studied. One isolate of Mycogone rosae was also included. Aleuriospore and phialospore morphology varied among the isolates as did other characteristics, but M. rosae was the only isolate to produce a red colouration of the medium. Growth was also variable, with three isolates of M. pemiciosa growing at about half the rate of the fastest. The slow‐growing isolates contained virus‐like particles, 36 nm diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 17 publications
0
28
1
Order By: Relevance
“…Our research concern- ing colony pigmentation on agar medium and pathogenicity of the isolates showed that CBS isolate (a weakly pathogenic against A15 strain of A. bisporus) is characterised with a slow-growing and little pigmented colony, while M9 (strongly pathogenic isolate) and M19 (weakly pathogenic) produced equally brown pigmented colony agar media. Atkey et al (1976) and Fletcher et al (1995) found that all studied isolates were highly pathogenic irrespective of the growth rate and virus particle content. It seems that the virulence in M. perniciosa isolates reveal a complex interaction between genotypes of pathogen and the host.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our research concern- ing colony pigmentation on agar medium and pathogenicity of the isolates showed that CBS isolate (a weakly pathogenic against A15 strain of A. bisporus) is characterised with a slow-growing and little pigmented colony, while M9 (strongly pathogenic isolate) and M19 (weakly pathogenic) produced equally brown pigmented colony agar media. Atkey et al (1976) and Fletcher et al (1995) found that all studied isolates were highly pathogenic irrespective of the growth rate and virus particle content. It seems that the virulence in M. perniciosa isolates reveal a complex interaction between genotypes of pathogen and the host.…”
Section: Resultsmentioning
confidence: 99%
“…Variability in the pathogenicity of M. perniciosa isolates can be attributable to the presence of mycoviruses in hyphae of these isolates (Fletcher et al 1995;Lapierre et al 1971;Umar et al 2000). Umar et al (2000) observed intracellular virus-like particles in scanning electron microscope.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It hampers the yield [75][76].The mycopathogen adheres to and penetrates A. bisporus during any stage of fruiting body development causing either the characteristic undifferentiated lumps of primordia or the fruiting body's color changes to brown. These tumorous bodies are covered with wet bubbles, white and fluffy mycelium, and amber droplets [77][78]. In commercial cultivation, M. perniciosa can commonly causes yield losses of about 15-30 percent once WBD develops.…”
Section: Mites As Vector Of Diseasesmentioning
confidence: 99%